Optimalisasi Kesiapan Penggunaan SIMRS di RSUD Kanjuruhan: Analisis Berdasarkan Extended Technology Acceptance Model - Dita, Janny; Peristiowati, Yuly; Prasetyo, Joko (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: This study aims to analyze the factors influencing the readiness to use the Hospital Management Information System (HMIS) at RSUD Kanjuruhan based on the Extended Technology Acceptance Model (TAM). Methods: A cross-sectional study design was employed, involving 220 healthcare workers selected from a total population of 424 using proportional random sampling. The variables examined included subjective norm, perceived usefulness, perceived ease of use, intention to use, and usage behavior. Data were collected through an online questionnaire and analyzed using simple linear regression. Results: Subjective norm significantly influenced perceived usefulness (R²=0.374) and perceived ease of use (R²=0.544). Both perceived usefulness (R²=0.592) and perceived ease of use (R²=0.056) affected the intention to use, which in turn had a significant impact on usage behavior (R²=0.448). Perceived usefulness emerged as the strongest predictor of the intention to use HMIS. Conclusion: Managerial support is essential to strengthen social norms, enhance understanding of HMIS benefits among healthcare workers, and optimize training and system features to support the integration of technology into hospital work culture.